Analisis Fonetik dan Fonologis Realisasi Vokal dan Konsonan Bahasa Indonesia di Empat Dialek - Andi Sahtiani Jahrir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Indonesian, as Indonesia's national language, plays a crucial role as a unifying tool in a diverse and multilingual nation. Its functions extend to intercultural communication, knowledge transmission, and the reinforcement of social values. However, the reality of Indonesian language use reveals significant phonetic variations, particularly in the realization of vowel and consonant phonemes. These variations, rooted in the influence of speakers' dialects, reflect the complexity and richness of Indonesia's phonological system. Employing a qualitative descriptive approach and contrastive analysis, data were collected through oral readings of the Malin Kundang folk tale by native speakers of each dialect. Analysis revealed significant variations in phoneme realization, triggered by various linguistic and sociolinguistic factors. Phoneme substitution was observed, for example, /z/ being replaced by /j/ (Bima) or /s/ (Jeneponto, Kendari), reflecting adaptation to the local phoneme inventory. Phoneme elision, particularly /h/ and /k/ at the end of words, indicates a tendency towards articulatory economy in informal spoken language. Phonological assimilation was evident in the change of /n/ to /ŋ/ in Jeneponto, influenced by Makassar phonotactics. Reduction or elision of the vowel /e/ in some dialects shows variations in vowel reduction strategies.